Optimizing Prison Law Enforcement to Prevent Recidivism - Muhammad Rizki Manurung; Ismail Koto (Abdurrauf Social Science, 2026)
Recidivism of inmates in Indonesian prisons is still a serious problem, especially related to narcotics abuse and possession of illegal communication devices. This phenomenon shows that there are gaps in the law enforcement system and coaching programs, which has implications for the low effectiveness of rehabilitation and the risk of repetition of criminal acts. This study aims to analyze the optimization of prison law enforcement as a strategy to prevent recidivism of inmates. The method used is library research with the collection of primary and secondary data from literature, books, journals, official reports, and previous research related to the correctional system, criminal law, and inmate development programs. Data is analyzed using content analysis techniques to identify patterns, relationships, and important information relevant to the research objectives. Research findings show that formal law enforcement without the support of a holistic coaching program tends to be less effective in preventing recidivism. The integration between strict disciplinary sanctions, educational coaching, psychological rehabilitation, and inmate independence training has proven to be more effective in reducing the risk of repetition of criminal acts. This research provides a basis for the development of correctional policies that are more responsive, fair, and oriented towards the social reintegration of prisoners, while enriching the study of correctional law theoretically and practically.